2018
DOI: 10.12659/msm.907496
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Long Intergenic Non-Coding RNA (lincRNA) of the NED25 Gene Modulates the microRNA-125b, STAT3, Nitric Oxide, and Procalcitonin Signaling Pathways in Patients with Sepsis

Abstract: BackgroundThe aim of this study was to investigate the long intergenic non-coding RNA (lincRNA) of the NED25 gene, and the microRNA (miR)-125b, STAT3, nitric oxide (NO), and procalcitonin (PCT) pathway in sepsis.Material/MethodsSeventy-five age-matched and sex-matched patients were divided into three groups: 25 patients with sepsis only; 25 patients with septic shock; and 25 healthy control subjects. Computational analysis and a luciferase assay confirmed that the STAT3 and PCT genes were target genes of miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…In healthy individuals all these component peptides, including PCT, are present at very low serum concentrations, and are produced by the neuroendocrine cells in the lungs and thyroid gland (26). Recent papers have studied the possible relationship between calcitonin or PCT and miRNAs (27,28,29,30). miRNAs are implicated in biological processes such as cellular differentiation, proliferation, and apoptosis; they are stable and can be detected in clinical samples and used as biomarkers for the early diagnosis of several diseases (31).…”
Section: Types Of Calcitonin Pro-calcitonin and Molecular Aspects MImentioning
confidence: 99%
“…In healthy individuals all these component peptides, including PCT, are present at very low serum concentrations, and are produced by the neuroendocrine cells in the lungs and thyroid gland (26). Recent papers have studied the possible relationship between calcitonin or PCT and miRNAs (27,28,29,30). miRNAs are implicated in biological processes such as cellular differentiation, proliferation, and apoptosis; they are stable and can be detected in clinical samples and used as biomarkers for the early diagnosis of several diseases (31).…”
Section: Types Of Calcitonin Pro-calcitonin and Molecular Aspects MImentioning
confidence: 99%
“…Meanwhile, by performing an ROC analysis, we found that only miR-125b and PCT were involved in post-operative infection. Previously, researches have exhibited that the treatment with LPS for the PBMs enhanced the PCT level and decreased the miR-125b level [19]. In addition, the treatment with LPS enhanced the expression of total STAT3 and phosphorylated STAT3, which in turn increased the expression level of PCT [19].…”
Section: Discussionmentioning
confidence: 97%
“…Previously, researches have exhibited that the treatment with LPS for the PBMs enhanced the PCT level and decreased the miR-125b level [19]. In addition, the treatment with LPS enhanced the expression of total STAT3 and phosphorylated STAT3, which in turn increased the expression level of PCT [19]. Nevertheless, previously, it has been indicated that miR-125b and the lincRNA of the gene of NED25 increased the levels of total STAT3 and phosphorylated STAT3 while lowering the expression level of PCT [20].…”
Section: Discussionmentioning
confidence: 99%
“…What is clear is that they influence the transcription, and ultimately translation, of many genes in the aetiologies of different cancers 86,87 and other diseases. 88 As can be seen from Table 1 and Figure 2, depending on the base present, SNP rs694539 changes the sequences of 4 transcripts, and rs2256292 and rs1941404 also alter multiple transcripts. Of the 8 transcripts emanating from the 2 forms of NNMT , only 1 transcript ( NNMT-201 ) goes on to be translated to any significant extent.…”
Section: Nnmt – Association With Homocysteine Metabolism and Illnessmentioning
confidence: 98%